Hot to trot - Beaton, M. C.; Green, R. W., (Novelist) (Beaton, M. C. Agatha Raisin mystery., 2020)
Jealously investigating an ex's intended, Agatha Raisin crashes the wedding only to become implicated in the bride's murder, a situation that immerses Agatha in the cutthroat equestrian world.